Gene expression association study in feline mammary carcinomas - Ferreira, Daniela (2019)
Works on cancer-related genes expression using feline mammary carcinomas (FMCs) are scarce but crucial, not only to validate these tumours as models for human breast cancer studies but also to improve small animal practice. Here, the expression of the cancer-related genes TP53, CCND1, FUS, YBX1, PTBP1, c-MYC and PKM2 was evaluated by real-time RT-qPCR, in a population of FMCs clinically characterized and compared with the disease-free tissue of the same individual. In most of the FMCs analysed, RNA quantification revealed normal expression levels for TP53, c-MYC, YBX1 and FUS, but overexpression in the genes CCND1, PTBP1 and PKM2. The expression levels of these cancer-related genes are strongly correlated with each other, with exception of c-MYC and PKM2 genes. The integration of clinicopathological data with the transcriptional levels revealed several associations. The oral contraceptive administration showed to be positively related with the TP53, YBX1, CCND1, FUS and PTBP1 RNA levels. Positive associations were found between tumour size and YBX1 RNA, and lymph node metastasis with c-MYC RNA levels. This work allowed to verify that many of these cancer-related genes are associated but may also, indirectly, influence other genes, creating a complex molecular cancer network that in the future can provide new cancer biomarkers.